2016
DOI: 10.1177/0265813516658886
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive planning: Generating conditions for urban adaptability. Lessons from Dutch organic development strategies

Abstract: The development of cities includes a wide variety of uncertainties which challenge spatial planners and decision makers. In response, planning approaches which move away from the ambition to achieve predefined outcomes are being explored in the literature. One of them is an adaptive approach to planning. In this paper, we argue that adaptive planning comes with a shift in focus. Instead of content and process, it is first of all about creating conditions for development which support a city’s capacity to respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(53 citation statements)
references
References 50 publications
0
50
0
3
Order By: Relevance
“…However, through the leadership of OA, and with the support of community members, access routes were created to improve accessibility. In such a situation, it is concluded that self-governance and civic initiatives provide ways to open up command and control planning systems to allow for more diverse urban configurations in African countries, and to increase the opportunities for incorporating anticipated and unanticipated changes during urban development (see also Rauws & De Roo, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, through the leadership of OA, and with the support of community members, access routes were created to improve accessibility. In such a situation, it is concluded that self-governance and civic initiatives provide ways to open up command and control planning systems to allow for more diverse urban configurations in African countries, and to increase the opportunities for incorporating anticipated and unanticipated changes during urban development (see also Rauws & De Roo, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…An emerging view amongst urban theorists and researchers is that effective functioning of urban areas should embrace uncertainties, multiple possible alternative futures and flexible decisions (Albrechts, 2006;De Roo, 2010;Korah et al, 2017;Rauws et al 2014) and further allows for self-organisation and self-governance (see Alfasi & Portugali, 2007;De Roo, 2016;Korah et al, 2016;Rauws et al 2016;Rauws, 2016;Boonstra, 2015). Self-governed civic initiatives in spatial planning require urgent attention particularly in Africa and other developing countries where in Roy's (2005) view, most of the major urban transformations of the 21 st century are likely to occur.…”
Section: Introductionmentioning
confidence: 99%
“…However, in making cities more responsive to change, we argue that the first and crucial step can be taken by redirecting the focus of planning to influencing and generating conditions under which development trajectories unfold. We call this an adaptive approach to planning (Rauws, De Roo 2016;Yamu et al 2016).…”
Section: Towards An Adaptive Approach For Guiding Urban Transformationsmentioning
confidence: 99%
“…Setting conditions cannot and should not be done in isolation from societal values, norms and agreements (including political agreements), for example on poverty reduction or protection of vulnerable ecosystems. Collective ambitions on creating a better future -one which is, for instance, believed to be more socially just, economically viable or climate change proofshould also be part of planning frameworks (Rauws, De Roo 2016). However, a risk of looking ahead is that the produced images and persuasive stories on potential futures are again translated into plans that project a particular future urban configuration.…”
Section: Conditions For Guiding Spatiofunctional Transformationsmentioning
confidence: 99%
“…The authors of this paper are convinced that there is a need to open up control-oriented planning practices to more adaptive approaches to planning. Rauws and De Roo (2016), they explore how Organic Development Strategies (ODS) can be more responsive in tackling the wide variety of uncertainties which challenge spatial planners and decision makers. The current approach in Malaysia of using assessment tools and scoring methods to enable local and state governments to optimise land use and transport integration, as well as approve TOD applications for development is questionable.…”
Section: Introductionmentioning
confidence: 99%